Analysis of Health Service Quality in BPJS Patient Satisfaction at the Inpatient Installation of RSU Sundari Medan - Chairunnisyah Nurma Difhanny; Dewi Agustina (Universitas Ibn Khaldun Bogor, 2023)
Research on the Sundari General Hospital in Medan was carried out in 2023 to get a picture of the quality of health services in terms of BPJS patient satisfaction. The method used is a descriptive method with qualitative research. The number of informants in the study was sixteen (16), namely 7 main informants and 9 triangulation informants who werel BPJS patients, patient family, and health workers, in depth interviews were conducted in the form of an open questionnaire. The results of the research carried out stated that health services at RSU Sundari Medan were not running optimally. Of the five aspects of patient satisfaction, two aspects of patient satisfaction are not optimal in supporting this. These two things are the condition of toilets that smell, the use of bed sheets that are rarely changed making patients uncomfortable, and doctors who are often late. Suggestions for related agencies to pay more attention to cleanliness, especially in toilets and the use of bed linen, and to improve performance, especially for doctors who will visit patients.